Originalités biogéographiques et atlas de la faune sauvage du Nunavik (Québec, Canada) - Sarrazin, Gaël (HAL CCSD, 2023)
This work focuses on the mammals and birds of Nunavik. This is the northernmost region of Quebec, beyond the 55th parallel north. This area is little known to naturalists, unlike other more northerly or southerly territories equipped with scientific study stations. The interest of this study lies in the lack of knowledge of the region's wildlife. The aim of this work is to determine the biogeographical originalities of Nunavik from a faunistic point of view in comparison with the rest of North America, but also to find out which species are present on the territory and their distribution.It would appear that Nunavik is a territory of transition between arctic and forest species. In terms of species distribution, at least 156 species are thought to inhabit the region, most of them in the southern half of Nunavik. Extreme climatic conditions at high latitudes and the absence of forest cover limit the expansion of all species over the entire territory. In addition, 79% of species appear to be reaching the limits of their range on the territory. This reinforces our concern that faunal assemblages could be completely overhauled by the end of the century. In other words, the disappearance of traditional arctic species in favor of forest species, to the detriment of (sub)arctic tundra species. Ce travail s'intéresse aux mammifères et oiseaux du Nunavik. Il s'agit de la région la plus au nord du Québec, au-delà du 55ème parallèle nord. Cette zone est peu connue des naturalistes contrairement à d'autres territoires plus septentrionaux ou méridionaux équipés de stations d'études scientifiques. L'intérêt de cette étude réside dans le manque de connaissances qui couvre la région concernant la faune sauvage. L'objectif de ce travail est de déterminer les originalités biogéographiques du Nunavik d'un point de vue faunistique, en comparaison avec le reste de l'Amérique du Nord, mais aussi de connaître les espèces présentes sur le territoire et leur répartition. Il semblerait que le Nunavik soit un territoire de transition ...